The Maturation of a Discipline: Celebrating the Journal’s 10-Year Anniversary - Walker, Bethany J. (Journal of Islamic Archaeology, 2023)
In celebration of the ten-year anniversary of the journal, this brief editorial note reviews the ways the field of Islamic archaeology has developed in the last decade, and the ways in which the journal has generated growth, facilitated innovation and collaboration, and given visibility to the field.